PERANCANGAN BOILER DENGAN MEMANFAATKAN SAMPAH KERING UNTUK BAHAN BAKAR PLTU MINI 3 kW STT-PLN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Boiler is a heat exchanger that serves to evaporate boiler feed water to produce dry steam to drive the turbines in order to produce electricity. The fuels used in this study are dry wastes such as paper, plastic, and wood. The process of designing this boiler is carried out so that the use of diesel to generate steam on energy conversion practicum/experiment in STT-PLN is no longer needed. Instead, they can use dry waste as fuel to produce steam which later will drive the turbines. The residue of burning waste process in the form of ashes is approximately 0.053% of the weight or volume of dry waste before burnt. The calculation conducted on this works is to determine the design of evaporator and economizer pipe. The calculation is also adjusted to the generated steam needed in order to spin the turbines. The pressure produced from this boiler design should be 2.9 bar and for the amount of steam was 21 kg / hour. As a result, the calculation of evaporator surface area is 8,83 m2, result simulation HTRI 8.95m2 with 88 pipes and 1500 mm for each pipe, while the heated surface area for economizer is 0,46 m2 result simulation HTRI 0,45 m2 with 18 pipes and 400 mm long for each pipe.